Arbuscular mycorrhizal fungi community composition, richness and diversity on enset (Ensete ventricosum (Welw.) Cheesman) in Ethiopia is influenced by manure application intensity in low‑input farming systems - Garo, G.; Geel, M. van; Eshetu, F.; Swennen, Rony L.; Honnay, O.; Vancampenhout, Karen (Springer, 2022)
Aims In low-input agricultural systems, arbuscular mycorrhizal fungi (AMF) play a role in plant nutrition, protection and water use. Evaluating how agricultural practices affect the composition of AMF communities is therefore an important step towards sustainable intensification. We characterized the AMF communities in enset (Ensete ventricosum) roots in smallholder enset-based farming systems in south Ethiopia and assessed the effects of soil fertility management on those communities.